Payment of Salaries Below the Minimum Wage Standard by Uncorporated Companies - Riskianna Adelya (Jurnal Sostekmas: Jurnal Sosial, Teknologi, dan Pengabdian Masyarakat, 2025)
The inadequacy of wage provision for labor is one of the quite complex issues, especially in Indonesia.The unmet need for wages has led to the emergence of many societal phenomena to voice their rights.The research method used is normative juridical research, which seeks to solve problems based on applicable norms, particularly in the implementation of laws.Based on the discussion above, it can be concluded that businesses without legal entity status are required to provide wages in accordance with the regional minimum wage regulations.The provision of wages must be adjusted to meet the standard living needs of the community. Context: The provisions for salary payment must be adjusted to meet the standard feasibility needs of the community. Keywords: Salary; Company; Regional Minimum Wage, Text to translate: